Dynamic analysis of peripheral blood TCR β-chain CDR3 repertoire in occupational medicamentosa-like dermatitis due to trichloroethylene - Dafeng Lin (Nature Portfolio, 2021)
Abstract Previously, we had cross-sectionally explored the characteristics of T cell receptor (TCR) repertoires from occupational medicamentosa-like dermatitis due to trichloroethylene (OMDT) patients, now we further analyzed the dynamic features of OMDT TCR repertoires. Peripheral blood TCR β-chain complementarity-determining region 3 (CDR3) genes were detected with the high throughput sequencing in 24 OMDT cases in their acute, chronic and recovery stages, respectively, and in 24 trichloroethylene-exposed healthy controls. The TCR repertoire diversity, TRBV/TRBD/TRBJ gene usage and combination, frequencies of CDR3 nucleotide (nt) and amino acid (aa) sequences in the cases in different stages and in the controls were analyzed. TRBV6-4 and TRBV7-9 frequencies significantly differed between the cases and controls (both P < 6.1 × 10–4). TRBV6-4 combination with TRBJ2-1, TRBJ2-2, TRBJ2-3, and TRBJ2-6, and TRBV7-9 combination with TRBJ2-1 were associated with the stage by OMDT severity (all P < 0.001). Ten CDR3-nt and 7 CDR3-aa sequences in TRBV7-9-TRBJ2-1 combination and 1 CDR3-nt and 1 CDR3-aa sequences in TRBV6-4-TRBJ2-1 combination were identified as associated with the severity of OMDT (all P < 0.001). We revealed further how TCR repertoires vary with the severity in the development of OMDT, and severity-related TCRs may provide important therapeutic targets for OMDT in clinical practice.